Pengujian Black Box berbasis Equivalence Partitions pada Aplikasi Seleksi Promosi Kenaikan Jabatan - Krismadi, Adi; Lestari, Ana Fisca; Pitriyah, Anisah; Mardangga, I Wayan Putra Ardhie; Astuti, Muji; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2019)
To guarantee the application (software) Selection Promotion Preferment is free from errors, testing is needed to test the quality of the application. This application has a problem when delete data, then the application will be tested with the Equivalence Partition-based Black Box Method thoroughly regarding the use, benefits, and results found from the use of the software. In testing the software Selection Promotion Preferment using Weight Product Method consists of 6 forms. Equivalence Partition-based Black Box method tests the quality of the application that will be carried out by testing software documentation with the discovery of errors on each form that is divided into three error models, namely errors in Function, Data Structure and Interface. The results of this test, to ensure the quality of the Selection Promotion Preferment application is free from errors by finding unintentional errors in the Selection Promotion Preferment application.